Teacher’s Perception on Teaching Strategy and Its Effect Toward Students: Discovery Learning - Rahma, Alleyza Rahma; Putri Rezeki; Inda Lestari; Utami Dewi (Tadris Pendidikan Bahasa Inggris IAIN Langsa, 2023)
This journal aims to determine teachers' perceptions of discovery learning teaching strategies and how the effects of these strategies on students, because their perceptions have a very large influence on the successful implementation of learning. Strategy in teaching is needed in the teaching process. With learning strategies, teachers will find it easier to determine information and manage step by step learning that is carried out effectively. Learning strategies are also used to make learning activities more interesting, fun, and able to arouse the curiosity of students. The subjects of this study were 8 teachers aged 30-40 years. Data was collected by means of on-site interviews with English subject teachers. The types of research carried out are qualitative data through observation and interview. The results show that the discovery learning teaching strategy as an Indonesian English teaching model recommended in the 2013 curriculum is very useful for students and learning runs more effectively, because students are encouraged to be able to explore their own learning materials and the effect felt by students is that they feel more challenged and motivated. Have the satisfaction of having succeeded in discovering and exploring their own learning.